2016
DOI: 10.5395/rde.2016.41.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Apicoectomy of maxillary anterior teeth through a piezoelectric bony-window osteotomy: two case reports introducing a new technique to preserve cortical bone

Abstract: Two case reports describing a new technique of creating a repositionable piezoelectric bony window osteotomy during apicoectomy in order to preserve bone and act as an autologous graft for the surgical site are described. Endodontic microsurgery of anterior teeth with an intact cortical plate and large periapical lesion generally involves removal of a significant amount of healthy bone in order to enucleate the diseased tissue and manage root ends. In the reported cases, apicoectomy was performed on the latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Bonson et al found that clinically derived human gingival and periodontal ligament fibroblasts survived and proliferated in direct contact with MTA particles. The above studies are also supported by Balto, [2] who found that human periodontal ligament fibroblasts attached to MTA within4 h and then spread out over the surface during the subsequent 20 hours. [9] Careful use of bone trimmer allows soft tissue juxtaposition and healing.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Bonson et al found that clinically derived human gingival and periodontal ligament fibroblasts survived and proliferated in direct contact with MTA particles. The above studies are also supported by Balto, [2] who found that human periodontal ligament fibroblasts attached to MTA within4 h and then spread out over the surface during the subsequent 20 hours. [9] Careful use of bone trimmer allows soft tissue juxtaposition and healing.…”
Section: Discussionsupporting
confidence: 68%
“…[1] It is the recommended therapy for endodontically treated teeth with unresolved periapical lesions when the prognosis of non-surgical root canal treatment is questionable. [2] The traditional surgical endodontics involves root resection (45˚ bevel), retrograde preparation of canal using burs. According to literature, this technique has a success rate of approx 60%.…”
Section: Introductionmentioning
confidence: 99%
“…The reposition of the bone window has been described for several indications in oral surgery with favorable outcomes [14,[21][22][23][24][25][26][27][28], including its application for sinus floor elevation [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Guided endodontic microsurgery enables an accurate visualization; identification; and a more accessible, precise, and minimally invasive treatment permitting faster postoperative healing. [ 8 ] Osteotomy diameters <5 mm resulted in improved osseous healing compared with those in excess of 5 mm, which resulted in fibrous tissue formation and delayed healing. [ 9 ] During an apicoectomy procedure, freehand drilling deviation 70% of the time is 2 mm and 22% of the time is 3 mm; however, with guided approach, a deviation of 0.79 mm (0.33 mm standard deviation) has been noted,[ 10 ] enabling dentists without extensive surgical skills to achieve predictable results.…”
Section: Discussionmentioning
confidence: 99%